Historical Diets of Forage Fish and Juvenile Pacific Salmon in the Strait of Georgia, 1966–1968. Issue 1 (1st January 2016) - Osgood, Geoffrey J.; Kennedy, Laura A.; Holden, Jessica J.; Hertz, Eric; McKinnell, Skip; Juanes, Francis
Abstract: The Strait of Georgia, British Columbia, provides important feeding and rearing habitat for forage fish, such as Pacific Herring Clupea pallasii and Eulachon Thaleichthys pacificus as well as all species of North American Pacific salmon Oncorhynchus spp. during their juvenile out-migration. In recent decades, this region has undergone large-scale physical and biological changes. Pacific Herring and Pacific salmon populations have experienced dramatic population fluctuations, while Eulachon have failed to recover from precipitous declines in the 1990s. Archival records of stomach content data from the 1960s, collected primarily from juvenile Pacific salmon, Pacific Herring, and Eulachon, allowed us to investigate diet variability in these species 60 years ago. Consistent with contemporary reports, we found that all species except Eulachon had generalist diets. In contrast to recent studies finding that Pacific Herring are the most important fish prey, Eulachon were the most frequently consumed fish, occurring in 28% of all piscivorous fish stomachs. This suggests that Pacific Herring are an important component of some Pacific salmon diets now, but only because lipid-rich Eulachon are no longer available. Chinook Salmon O. tshawytscha and Coho Salmon O. kisutch had the most similar diets, in part because of their greater piscivory. Species, length, and month and year of capture showed some explanatory power in differentiating the diets of the fish, although they explained less than 10% of total diet variation. Historical data, such as those presented here, offer a unique opportunity to investigate temporal differences in foraging ecology, informing management on how changes in the Strait of Georgia ecosystem may impact the trophic interactions between species. Received September 30, 2015; accepted July 5, 2016